SC12 Mental health detention in the community: developing a meaningful simulation-based educational intervention. (3rd November 2019) - Houton, Paula; Reid, Helen; Gormley, Gerry
Abstract : Background: Simulation-based education in the area of mental health is under-utilized¹ One of the most challenging tasks a doctor can be faced with is deciding whether or not an unwell patient requires detention for assessment under relevant mental health legislation. This can be a highly emotional and difficult process for all involved before, during and after the event itself. General Practitioners are faced with this medical emergency in the community but despite this they get limited training and exposure to prepare them as they would for other medical emergencies. Other professionals involved also report limited formal training. There is therefore a need for the development of a simulation-based teaching intervention which can bridge this knowledge gap. This is a complex and sensitive clinical encounter and careful consideration must be given to ensure simulation content is authentic and meaningful.² Summary of project: In this research, we are using scoping review methodology to explore mental health detention processes in primary-care settings. We are particularly interested in learning more about unmet training needs and experiences of doctors and key stakeholders involved in this process. We have identified key stakeholders as the patient, the patient's wider support circle, GPs, social workers, the ambulance team, police-service, community mental health team and secondary care colleagues in psychiatry. Importantly, our scoping approach includes input from and consultation with stakeholder representatives throughout the project. Summary of results: We will present findings from our scoping review. Literature review indicates that there is very limited formal training in this area for any of the professionals involved. Despite this, there is widespread acknowledgment of the challenges associated with these situations in the community and of the potential benefits of interdisciplinary training. It is apparent that there is much we can learn from patients and families who have already been through this process. These findings will be augmented with results of our stakeholder consultation. Discussion, conclusions and recommendations: Our findings will help identify unmet training needs and will also provide key information that should be taken into consideration when developing simulation-based educational interventions to bridge this knowledge gap. It is anticipated that this work will serve as a foundation for the development of multidisciplinary, simulation-based learning activities in this area. Increasing the knowledge and experience of stakeholders will improve patient care and potentially lead to a reduction in associated stress and anxiety for all involved in this complex clinical encounter. References: Thomson A, Cross S, Key S, Jaye P, Iversen A. How we developed an emergency psychiatry training course for new residents using principles of high-fidelity simulation. Medical Teacher . 2013; 35(10): 797–800. Available from: DOI: 10.3109/0142159X.2013.803522 Nestel D, Krogh K, Kolbe M. Exploring realism in healthcare simulations. In: Nestel D, Kelly M, Jolly B, Watson M. (eds.) Healthcare simulation education: evidence, theory and practice. West Sussex: Wiley Blackwell; 2018. p23–28.